2010
DOI: 10.4061/2010/417314
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Hallmarks, Clinical Parallels, and Value for Drug Testing in Alzheimer's Disease of the APP[V717I] London Transgenic Mouse Model

Abstract: The APP[V717I] London (APP-Ld) mouse model recapitulates important pathological and clinical hallmarks of Alzheimer's disease (AD) and is therefore a valuable paradigm for evaluating therapeutic candidates. Historically, both the parenchymal and vascular amyloid deposits, and more recently, truncated and pyroglutamate-modified Abeta3(pE)-42 species, are perceived as important hallmarks of AD-pathology. Late stage symptoms are preceded by robust deficits in orientation and memory that correlate in time with Abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 43 publications
(70 reference statements)
6
34
2
Order By: Relevance
“…In animal models of AD, Ab42 is considered as the first peptide to be deposited in vessels, further entrapping massive amounts of soluble Ab40 peptide, and ultimately occurring extensive amyloid plaques in vascular plaques. 27 In addition, our previous findings have shown that TLJN reduces amyloidogenic processing of amyloid precursor protein in APP23 Tg mice. 29 At 3 months of age (prior to amyloid deposition), APP23 Tg mice exhibit activated microglia and astroglia, with a heightened inflammatory profile consisting of increased mRNA levels of interleukin (IL)-1b, IL-6, major histocompatibility complex II, and macrophage-colony stimulating factors.…”
Section: Discussionmentioning
confidence: 98%
“…In animal models of AD, Ab42 is considered as the first peptide to be deposited in vessels, further entrapping massive amounts of soluble Ab40 peptide, and ultimately occurring extensive amyloid plaques in vascular plaques. 27 In addition, our previous findings have shown that TLJN reduces amyloidogenic processing of amyloid precursor protein in APP23 Tg mice. 29 At 3 months of age (prior to amyloid deposition), APP23 Tg mice exhibit activated microglia and astroglia, with a heightened inflammatory profile consisting of increased mRNA levels of interleukin (IL)-1b, IL-6, major histocompatibility complex II, and macrophage-colony stimulating factors.…”
Section: Discussionmentioning
confidence: 98%
“…From about 3 months of age onwards, AβPPLon mice express soluble Aβ aggregates and develop cognitive impairment but they do not appreciably develop brain plaque until at least about 12 months of age and thus their cognitive impairment is dissociated from plaque formation [25, 26]. In order to evaluate the effects of E64d before and after brain plaque formation occurs, two age groups of transgenic AβPPLon mice were studied, young (6 to 9 months of age) and old (12 to 15 months of age).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of β-secretase inhibitors on wt β-secretase activity, brain plaque and memory deficits can be studied in transgenic mice expressing AβPP containing a mutation near the γ- secretase site sequence but which has the wt β-secretase site sequence. One such mutant AβPP is known as the London mutant (AβPPLon) and is found in 30 families, which develop familial AD [2426] (AD&FTD Mutation Database http://www.molgen.ua.ac.be/ADMutations). …”
Section: Introductionmentioning
confidence: 99%
“…The concentration of aggregated Ab in the cortex of drugtreated mice (n ¼ 7 per group) was measured using the Amorfix A 4 assay (Amorfix, Mississauga, Canada) as previously described (Tanghe et al, 2010). Tissues were homogenized (10% w/v) in 2% (v/v) nonyl phenoxylpolyethoxylethanol (NP-40) in PBS containing 1 mM phenylmethylsulfonyl fluoride and protease inhibitor cocktail (Complete Mini, Roche, Quebec, Canada).…”
Section: Ab Immunoassaysmentioning
confidence: 99%